ANALISIS PENERAPAN PENGELOLAAN RISIKO TINGKAT SUKU BUNGA BANKING DI BANK CIMB NIAGA - , Ray Bahren Siregar, SE ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to measure interest rate risk in banking book and its impact to Bankâs net interest income and steps to mitigate the risk. Total interest rate risk is measured from the implementation and result of fund transfer pricing that not only assess business units performance and product margin, but also effectively calculates interest rate risk arise from funding and lending activities. Research methods used for measuring interest rate risk in banking book is explanatory method using secondary data analysis. Data assessed are fund transfer pricing reports, movement of duration and present value of a basis point of products in Bankâs balance sheet in each quarter of 2009. Present value of a basis point value explains the sensitivity to Bankâs net interest income for 1 basis point change in market interest rate. Research results showed the amount of present value of a basis point in December 2009 at Rp 1.479 million, and the notional amount to mitigate the interest rate risk with interest rate swap is Rp 6.8 trillion.